Highly conserved elements discovered in vertebrates are present in non-syntenic loci of tunicates, act as enhancers and can be transcribed during development - Sanges, Remo; Hadzhiev, Yavor; Gueroult-Bellone, Marion; Roure, Agnes; Ferg, Marco; Meola, Nicola; Amore, Gabriele; Basu, Swaraj; Brown, Euan R.; De Simone, Marco; Petrera, Francesca; Licastro, Danilo; et al. (Nucleic acids research, 2013)
Co-option of cis-regulatory modules has been suggested as a mechanism for the evolution of expression sites during development. However, the extent and mechanisms involved in mobilization of cis-regulatory modules remains elusive. To trace the history of non-coding elements, which may represent candidate ancestral cis-regulatory modules affirmed during chordate evolution, we have searched for conserved elements in tunicate and vertebrate (Olfactores) genomes. We identified, for the first time, 183 non-coding sequences that are highly conserved between the two groups. Our results show that all but one element are conserved in non-syntenic regions between vertebrate and tunicate genomes, while being syntenic among vertebrates. Nevertheless, in all the groups, they are significantly associated with transcription factors showing specific functions fundamental to animal development, such as multicellular organism development and sequence-specific DNA binding. The majority of these regions map onto ultraconserved elements and we demonstrate that they can act as functional enhancers within the organism of origin, as well as in cross-transgenesis experiments, and that they are transcribed in extant species of Olfactores. We refer to the elements as ‘Olfactores conserved non-coding elements’.
Gesehen am 31.01.2022